IBADAH QURBAN DALAM PERSPEKTIF HADIS - Abdullah Nur (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
Joys and sorrows are inevitable in the course of human life, when in trouble, the man has always tried to get closer to something supernatural (which they call God), this approach is usually through sacrifice in the form of offerings, crops of fruit, or livestock like cows, buffalo, camel, or goat. By granting this sacrifice they expect all the problems of life they experience can be resolved, or at least be stopped and replaced with better ones. Islam has a system set up with the perfect execution of the sacrificial services ranging from requirements, law, animals can be used as a sacrifice, execution time, and so on.